ANALISIS PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PERUSAHAAN SEKTOR PERTAMBANGAN - I GUSTI AGUNG ARISTA PRADNYANI; PUTU ATIM PURWANINGRAT; I GUSTI AGUNG AYU PRAMITA INDRASWARI; NILA RAHAYU (GANEC SWARA, 2024)
This study aims to partially determine how liquidity, leverage, and profitability affect Financial Distress. The study was conducted on mining companies listed on the Indonesia Stock Exchange in 2020–2022. This study is a quantitative study and the sample was determined using a purposive sampling technique, namely the selection of samples with certain criteria that were set, so that a sample of 63 companies was obtained. The statistical analysis used includes the Normality test, multicollinearity, heteroscedasticity, autocorrelation test, determination coefficient test, F test and t test. Data analysis uses multiple linear regression analysis. After conducting the study, the results are Liquidity has a positive and significant effect on Financial Distress, Leverage has a negative and significant effect on Financial Distress, and Profitability has a negative and significant effect on Financial Distress.